Postnatal development of testis and epididymis, semen characteristics and fertility of Brown- Swiss Crossbred Bulls - Surendran Varma Raja C K (Department of Animal Reproduction and Gyneacology, College of Veterinary and Animal Sciences, 1981)
A systematic investigation involving the use of 24 Brown Swiss crossbred bull calves and 7 adult bulls with 62.5% exotic inheritance varying in age from 0- 360 days and 22-40 months respectively, resred and maintained at Indo-Swiss Project, Mattupatty, Kerala, was carried out in order to (a) trace the postnatal growth and development of the testis and epididymis and (b) assess the semen characteristics such as volume, initial motility, sperm concentration, live sperm count and incidence of abnormal sperms; As a corrolary to and as an integral part of this comprehensive study, 6679 semen collection particulars from the records maintained at the Indo-Swiss Project, Mattupatty and 7586 insemination data at the Crossbreeding Research Centre, Muvathuphza werecritically scrutinised to deduce freezability/discard rate of the ejaculates and the fertility potenoy of the bulls, respectively. The materials used, the salient observations made and the valid inferences drawn aare given below: Twenty four pairs of testis and epididymis collected from the bull calves were processed to study the postnatal growth and development. The pattern of growth of testis and of the epididymis was found to be curvilinear. The testicularand epididymal weights were observed to be significantly (p<0.01) correlated with the age, and body weight of the animals. A highly significant (p<0.01) correlation between epididymal weight and testicular weight was also observed. The growth rate of the seminiferous tubules appeared to be of sigmoid type. Formation of lumen in the seminiferous cords was initiated at 150 days and completed, at 180 days of age. The transformation of gonocytes to spermatogonia occurred at 150 days of age. The formation of primary spermatocytes, spermatid and spermatozoa cocurred at the age of 150 days, 300 days and 300-360 days, respectively. The process of transformation of supporting cells was initiated at 120 days and completed at 180 days of age. The transformation of immature Leydig cells to mature cells was initiated at 150 days and completed, by 180 days of age. There were distinct regional differences between the caput, the corpus and the cauda epididymis in respect of the diameter of the tubules, height of the epithelium and the degree of transformation of Epithelial lining from simple columnar to pseudostratified type. The distal part of the ductus epididymis seemed to have attained the adult size at an earlier age than the proximal. Sperms were seen in all the three regions at about 300 days. The mean values of ejaculate volume, initial motility, sperm concentration, live sperm count, sperm head abnormalities, tail abnormalities and proximal protoplasmic droplets were found to be 2.65 ± 0.84 ml, 66.24 ± 0.87%, 1599.64 ± 55.371 milions per ml of semen, 72.55 ± 1.310%, 4.91 ± 0.439%, 0.65 ± 0.045%, 6.47 ± 0.775% and 1.20 ± 0.143%, respectively. Significant (p<0.01) variations between bulls were observed in respect of sperm head abnormalities, tail abnormalities and proximal protoplasmic droplets and between months, in respect of ejaculate volume, sperm head abnormalities, free loose head, tail abnormalities and proximal protoplasmic droplets. Seasonal variation (p<0.05), however, was evident only in the incidence of tail abnormalities. Variations due to age of bulls were found to be significant (p<0.01) in the casse of ejaculate volume, sperm concentration, free loose head, middle piece abnormalities and tail abnormalities. The freezability of sperms expressed in terms of per cent of post-thawing motility was found to be 36.86. There was no seasonal effect on the freezability of sperms. The freezability rate increased significantly (p<0.01) with advancement of age of bulls. The overall rejection rate of the ejaculates was noted to be 39.80%. Most of the rejection (71.75%) was done before freezing. The pre-freezing rejection was found to be 28.55% of the total ejaculate. The post-freezing discard to be 15.74% of the frozen samples. The rejection rates of the ejaculates differed significantly (p<0.01) between months/seasons/age of the bulls. The rate of rejection was found to decrease with advancing age. The overall fertility rate of the bulls was found to be 56.06%. There were significant (p<0.01) differences in the fertility rate between months/seasons of insemination and between age of the bulls. As between bulls also, there was a significant variation (p<0.01) in the fertility rate. The significance of the observations inferences indicated above and their relevance to the implementation of cross breeding programme in Kerala were discussed briefly.